2019
DOI: 10.1186/s12889-019-6956-1
|View full text |Cite
|
Sign up to set email alerts
|

Homophobia and heteronormativity as dimensions of stigma that influence sexual risk behaviors among men who have sex with men (MSM) and women (MSMW) in Lima, Peru: a mixed-methods analysis

Abstract: Background Stigma differentially influences HIV and STI care among MSM, especially regarding partner notification practices. Recognizing the heterogeneous behaviors/identities within the category “MSM,” we used mixed-methods to assess sexual risk behaviors among men who have sex with men only (MSMO) and behaviorally bisexual MSM (MSMW) with HIV and/or other STIs. Methods MSMO/MSMW recently diagnosed (< 30 days) with HIV, syphilis, urethritis, or proctitis completed a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…77,79 Studies in Latin America corroborate the negative consequences of minority stress for HIV and mental health outcomes. Exposure to anti-MSM stigma is associated with mental health problems among MSM in Chile, Mexico, Brazil, and Peru, [80][81][82][83] and with HIV risk and prevention behaviours among MSM in El Salvador, Belize, and Guatemala. 36,84,85 A few studies have applied syndemic theory to examine health inequities among MSM in Colombia, Mexico, and Brazil.…”
Section: Socioecological Modelmentioning
confidence: 99%
“…77,79 Studies in Latin America corroborate the negative consequences of minority stress for HIV and mental health outcomes. Exposure to anti-MSM stigma is associated with mental health problems among MSM in Chile, Mexico, Brazil, and Peru, [80][81][82][83] and with HIV risk and prevention behaviours among MSM in El Salvador, Belize, and Guatemala. 36,84,85 A few studies have applied syndemic theory to examine health inequities among MSM in Colombia, Mexico, and Brazil.…”
Section: Socioecological Modelmentioning
confidence: 99%
“…( 2015 ), assessing LGB subjects in Belgium and Italy, found that social support is a protective mediator between IH and anxiety as well as depressive symptoms in their path-analysis model. Also, higher levels of IH and social heteronormativity have been associated with a significant increase of sexual risk behaviours and increased incidence of sexually transmitted diseases among LGBs (Perez-Brumer et al ., 2019 ).…”
Section: Homophobia and Mental Healthmentioning
confidence: 99%
“… 20–22 However, a systematic review and meta-analysis did not find a statistically significant relationship between the willingness to be vaccinated and gender identity. 11 Further, in other sexually transmitted disease-related studies, MSMW have demonstrated lower utilization rates of prevention and testing services relevant to the MSM population, 23 and have reported lower levels of sexual health knowledge and behavioral skills. 24 , 25 To our knowledge, few studies have revealed how underlying factors affect vaccination intention in these two populations and the variations among them, leading to a lack of appropriate recommendations for guidance.…”
Section: Introductionmentioning
confidence: 98%